Amblyomma sculptum Salivary Protease Inhibitors as Potential Anti-Tick Vaccines - Costa, Gabriel Cerqueira Alves; Ribeiro, Izabela Cosso Tavares; Melo-Junior, Otoni; Gontijo, Nelder F.; Sant’Anna, Mauricio R.V.; Pereira, Marcos H.; Pessoa, Grasielle C.D.; Koerich, Leonardo B.; Oliveira, Fabiano; Valenzuela, Jesus G.; Giunchetti, Rodolfo Cordeiro; Fujiwara, Ricardo Toshio; et al. (Frontiers in Immunology, 2021)
Amblyomma sculptum is the main tick associated with human bites in Brazil and the main vector of Rickettsia rickettsii, the causative agent of the most severe form of Brazilian spotted fever. Molecules produced in the salivary glands are directly related to feeding success and vector competence. In the present study, we identified sequences of A. sculptum salivary proteins that may be involved in hematophagy and selected three proteins that underwent functional characterization and evaluation as vaccine antigens. Among the three proteins selected, one contained a Kunitz_bovine pancreatic trypsin inhibitor domain (named AsKunitz) and the other two belonged to the 8.9 kDa and Basic Tail families of tick salivary proteins (named As8.9kDa and AsBasicTail). Expression of the mRNA encoding all three proteins was detected in the larvae, nymphs, and females at basal levels in unfed ticks and the expression levels increased after the start of feeding. Recombinant proteins rAs8.9kDa and rAsBasicTail inhibited the enzymatic activity of factor Xa, thrombin, and trypsin, whereas rAsKunitz inhibited only thrombin activity. All three recombinant proteins inhibited the hemolysis of both the classical and alternative pathways; this is the first description of tick members of the Kunitz and 8.9kDa families being inhibitors of the classical complement pathway. Mice immunization with recombinant proteins caused efficacies against A. sculptum females from 59.4% with rAsBasicTail immunization to more than 85% by immunization with rAsKunitz and rAs8.9kDa. The mortality of nymphs fed on immunized mice reached 70 -100%. Therefore, all three proteins are potential antigens with the possibility of becoming a new tool in the control of A. sculptum.